THE ANOGENITAL CONDYLOMAS. ETIOLOGY, CLINICAL SYMPTOMS, TREATMENT, PROPHYLAXIS - M.G. Galitskaya (Вопросы современной педиатрии, 2009)
The article is dedicated to the one of the most frequent clinical manifestations of papillomavirus infections – the anogenital condylomas. It is known fact, that viral papilloma infection is the most prevalent sexually transmitted infections. The author described clinical signs of genital condylomas and proved the urgency of this problem. Taking into account low effectiveness of treatment, the unique opportunity of initial specific prophylaxis of a disease with vaccination is observed.Key words: papillomavirus infections, anogenital condylomas, vaccine prophylaxis.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(6):113-116)